2005
DOI: 10.1016/j.euroecorev.2004.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of a labour supply function using alternative measures of hours of work

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…One finding from the new surveys is that estimates of labor supply elasticities may be sensitive to the methods used to collect the underlying data. Klevmarken's (2005) analysis of the Swedish Household Panel Surveys revealed that own wage elasticities estimated using weekday time-diary data were larger than those estimated using retrospective annual work hours questions but similar to those estimated from previous-week recall questions. Within the time diaries,…”
Section: Literature Reviewmentioning
confidence: 99%
“…One finding from the new surveys is that estimates of labor supply elasticities may be sensitive to the methods used to collect the underlying data. Klevmarken's (2005) analysis of the Swedish Household Panel Surveys revealed that own wage elasticities estimated using weekday time-diary data were larger than those estimated using retrospective annual work hours questions but similar to those estimated from previous-week recall questions. Within the time diaries,…”
Section: Literature Reviewmentioning
confidence: 99%
“…An extensive literature confirms the reliability and validity of diary data and their superiority over other time-use surveys based on stylized questions, asking respondents to estimate time in activities on a 'typical day' (Juster and Stafford, 1985;Robinson and Godbey, 1999;Bianchi et al, 2006;Kalenkoski and Pabilonia, 2012). In the labour supply literature, for example, Klevmarken (2005) argues that information on actual hours of work from time-use surveys is more relevant than normal hours or contracted hours generally reported in stylized questions. The author shows that time-use data yields much smaller estimates of wage-rate effects compared to measures of normal hours of work, which may have important implications for tax policy design, among others.…”
Section: Data and Variablesmentioning
confidence: 93%
“…2 Yet few papers focus on the implications of such discussion. One exception is Klevmarken's (2005) investigation of how the choice of data source and the applied measurement technique of paid work affect wage rate elasticities and income elasticities. Specifically, his study shows that the time-use data collection method strongly influences the estimates of wage rate effects on labour supply, especially when weekend work is taken into account.…”
Section: Previous Researchmentioning
confidence: 99%